Quality characterization of Andean blackberry fruits (Rubus glaucus Benth.) in different maturity stages in Antioquia, Colombia (2015)
Product quality and safety are two essential characteristics for the fruit market, making it necessary to normalize and standardize processes in order to improve their commercialization. In this study, the quality of two Andean blackberry cultivars grown in two regions of Antioquia (Envigado and Guarne), Colombia, from different maturity stages as defined by the Norma Tecnica Colombiana 7146 (NTC Spanish) was characterized. The parameters that were found suitable for the fruit quality characterization were: weight, total solid soluble content (TSS), titratable acidity (TA), maturity index (MI), color index (CI) and firmness (F). The equatorial diameter (ED) maintained its importance relative to the standard and the market, along with the juice yield (JY). The quotient a*/b* presented the best correlation with the visual color scale as defined in the standard. The TSS ranges defined in NTC 4106 were not verified in this studied for fruits grown in the agroclimatic conditions of Antioquia. Linear regression models are a useful tool for making quick and easy comparisons and estimations of the quality parameters.